QUANTIFICATION OF ANTICOAGULANTS DABIGATRAN, RIVAROXABAN, AND PRASUGREL BY CHROMATOGRAPHIC AND SPECTROMETRIC TECHNIQUES – REVIEW - SATYA PRASAD B; JAYAKUMARI S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
A review is presented on different analytical techniques used for quantitative analysis of selected anticoagulants dabigatran, rivaroxaban, and prasugrel. Efforts have been made to collate all the relevant references to the extent possible. The review discusses the advantages and disadvantages of the cited analytical techniques, which will help to give insights into the methods used for estimation of selected anticoagulants such as dabigatran, rivaroxaban, and prasugrel, from clinical isolates, and its dosage forms. The review highlights the basic as well as advanced techniques performed for estimating dabigatran, rivaroxaban, and prasugrel. The techniques illustrated here have been demonstrated to be useful for quantitative determination of selected anticoagulants and may find application in analyzing other related properties.